Benefits of Gardenia jasminoides Ellis’s floral volatile components on human emotions and moods - Yan Cai; Hannan Chen; Xin Zhang; Wanning Bu; Wei Ning (Scientific Reports)
Abstract With the advancement of society, there has been an increasing focus on the health status of college students, with plants playing a significant role in the campus environment. Investigating the impact of the aromatic scent of plants on the physical and mental well-being of college students is essential. This study centered on the common indoor potted flower Gardenia jasminoides Ellis to delve into its aroma and the influence of its volatiles on the physical, mental, and emotional recovery of college students. The findings revealed that the subjects in both the olfactory group (G1) and the control group (G2) exhibited a decrease in blood pressure, pulse, β wave power, and skin electrical signal, alongside an increase in α wave power and heart rate variability (HRV) index. Notably, G1 saw a rise in α wave power by 0.17 µV2/Hz and G2 experienced an increase in HRV index by 0.184, while the power of β wave decreased by 2.589 and 0.01 µV2/Hz, respectively. Moreover, psychological indicators showed a significant increase in ‘energy’ and ‘self’ scores for both G1 and G2. Additionally, the perception of gardenia odor by college students was found to be associated with various physiological and psychological indicators in the experiment. The study highlighted that the volatiles of Gardenia jasminoides Ellis are rich in terpenes and alcohols, with terpenes playing a role in blood pressure regulation and relaxation, while alcohols like linalool contribute to air freshness, nervous system regulation, and sedative effects. The findings of our research offer backing for utilizing aromatic plants with terpenes and alcohols, such as gardenia, to enhance their health-promoting properties.